2009
DOI: 10.1038/ncb1973
|View full text |Cite
|
Sign up to set email alerts
|

Localized and reversible TGFβ signalling switches breast cancer cells from cohesive to single cell motility

Abstract: Here we use intravital imaging to demonstrate a reversible transition to a motile state as breast cancer cells spread. Imaging primary tumours reveals heterogeneity in cell morphology and motility. Two distinct modes of motility are observed: collective and single-celled. By monitoring the localisation of Smad2 and the activity of a TGFβ-dependent reporter gene during breast cancer cell dissemination we demonstrate that TGFβ signalling is transiently and locally activated in motile single cells. TGFβ1 switches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
514
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(548 citation statements)
references
References 35 publications
29
514
0
5
Order By: Relevance
“…94 Transforming growth factor b signaling may be essential in the selection of cohesive or single-cell migration pattern by metastatic cells. 95 To reach the lymphatic vessel, the migrating cells need to sense direction in the extracellular environment. The coming together of the cells and the vessel may occur owing to their migration or growth toward each other.…”
Section: The Role Of Vegfs In Lymphangiogenesismentioning
confidence: 99%
“…94 Transforming growth factor b signaling may be essential in the selection of cohesive or single-cell migration pattern by metastatic cells. 95 To reach the lymphatic vessel, the migrating cells need to sense direction in the extracellular environment. The coming together of the cells and the vessel may occur owing to their migration or growth toward each other.…”
Section: The Role Of Vegfs In Lymphangiogenesismentioning
confidence: 99%
“…Recently, it has been reported that p130CAS over-expression in mammary epithelial cells (MECs) shifts TGF signalling from SMAD2/SMAD3 phosphorylation to p38 MAPK activation, rendering MECs resistant to TGF-induced growth arrest and enhancing their metastatic potential 73 . Notably, NEDD9 was found to be a new transcriptional target of TGF signalling in highly metastatic mammary adenocarcinoma cells that switch from collective motility to single cell motility, and its silencing results in inhibition of amoeboid motility in response to TGF 74 . Overall, CAS family can act as a molecular rheostat that switches the tumour suppressor function of TGF to a pro-metastatic role during breast cancer progression.…”
Section: Migration and Invasionmentioning
confidence: 99%
“…It often involves transforming growth factor (TGF)-b and SMAD (Derynck and Akhurst, 2007). EMT cells are presumed to be responsible for metastasis (Leroy et al, 1994;Christiansen and Rajasekaran, 2006;Alexander et al, 2008;Giampieri et al, 2009;Martello et al, 2010;Pantel and Alix-Panabieres, 2010). Here are some recent arguments for this statement.…”
Section: Epithelial-to-mesenchymal Transitionmentioning
confidence: 99%
“…Solitary, presumably EMT cells (5%), of carcinoma move much more rapidly in vivo than the collective clusters, and, induced by TGF-b, intravasate into the blood vessels, whereas clusters rather invade the lymph modes (as induced by epidermal growth factor (EGF; Giampieri et al, 2009). The motile single-cell invasions of blood vessels by rat breast carcinoma has been beautifully demonstrated (Giampieri et al, 2009;Campbell et al, 2010). Solitary cell infiltration in pancreatic cancer is a good indication of the gravity and poor prognosis of the cancer (Masugi et al, 2010).…”
Section: Epithelial-to-mesenchymal Transitionmentioning
confidence: 99%